2000
DOI: 10.3109/01677060009083481
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitter Levels and Synaptic Strength at theDrosophilaLarval Neuromuscular Junction are not Altered by Mutation in theSluggish-aGene, Which Encodes Proline Oxidase and Affects Adult Locomotion

Abstract: The sluggish-A (slgA) gene of Drosophila melanogaster has been shown to encode for the enzyme proline oxidase, a mitochondrial enzyme which catalyzes the first step in the conversion of L-proline to L-glutamate. The slgA transcript is expressed in both larval and adult Drosophila melanogaster. Mutations in this gene lead to reduced proline oxidase activity and an elevation of free proline levels. Adult mutant flies show a striking reduction of motor activity. Since proline oxidase may contribute to the supply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…However, we failed to demonstrate immunolabeling either in any of the B1-4 motoneurons or in the salivary gland itself. GLU is also the principal excitatory neurotransmitter in motoneurons of arthropods (Johansen et al, 1989;Usherwood, 1994;Shupliakov et al, 1995, Burrows, 1996Shayan et al, 2000).…”
Section: Glu Appears To Be Involved In Both Afferent and Efferent Evementioning
confidence: 99%
“…However, we failed to demonstrate immunolabeling either in any of the B1-4 motoneurons or in the salivary gland itself. GLU is also the principal excitatory neurotransmitter in motoneurons of arthropods (Johansen et al, 1989;Usherwood, 1994;Shupliakov et al, 1995, Burrows, 1996Shayan et al, 2000).…”
Section: Glu Appears To Be Involved In Both Afferent and Efferent Evementioning
confidence: 99%
“…Dietary ingestion of bacterially expressed LdProDH ‐dsRNA significantly decreased its mRNA level, and caused an elevation of free proline content in the hemolymph of L. decemlineata adults. Consistent with our results, mutations in this gene lead to reduced proline oxidase activity and hyperprolinemia in both D. melanogaster (Hayward et al ., ; Shayan et al ., ) and human beings (Jacquet et al ., ). Thus, our results indicated that LdProDH protein should catalyze proline catabolism in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, the putative genes encoding ProDH-like proteins have been completely or partially cloned in Drosophila melanogaster (Hayward et al, 1993) and 11 other Drosophila species (Richards et al, 2005;Clark et al, 2007;Ranz et al, 2007), Anopheles gambiae (Holt et al, 2002), Aedes aegypti (Nene et al, 2007), Culex quinquefasciatus (XM_001851357.1), Apis mellifera (XM_395275.3), Tribolium castaneum (Richards et al, 2008), Pediculus humanus corporis (DS235321.1) and Acyrthosiphon pisum (XM_001950466.1). Mutations in this gene lead to reduced proline oxidase activity and an elevation of free proline levels in D. melanogaster (Hayward et al, 1993;Shayan et al, 2000) and human beings (Jacquet et al, 2002). Moreover, D. melanogaster mutant adults greatly decrease their motor activity (Shayan et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation